The Palgrave Concise Historical Atlas of the First World War - Hughes, M.; Philpott, W.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2005)
The First World War continues to fascinate. Its profound effect on politics and society is still felt today. Yet it remains a greatly misunderstood conflict, shrouded in myths and misperceptions. In The Palgrave Concise Historical Atlas of the First World War Philpott and Hughes, leading young historians of the conflict, draw on recent scholarship to present a clear introduction to the war. In fifty maps, accompanied by supporting text and statistical tables, they survey the main battles and political features of the war. This concise volume will give students and general readers important insights into the nature and effects of world war.
Keywords: Europe—History.; History, Modern; Military history; World history; World War, 1939-1945.; European History; Modern History; History of Military; World History, Global and Transnational History; History of World War II and the Holocaust